Altered Functions of Neutrophils in Two Chinese Patients With Severe Congenital Neutropenia Type 4 Caused by G6PC3 Mutations - Dai, Rongxin; Lv, Ge; Li, Wenyan; Tang, Wenjing; Chen, Junjie; Liu, Qiao; Yang, Lu; Zhang, Min; Tian, Zhirui; Zhou, Lina; Yan, Xin; Wang, Yating; et al. (Frontiers in Immunology, 2021)
Background: SCN4 is an autosomal recessive disease caused by mutations in the G6PC3 gene. The clinical, molecular, and immunological features; function of neutrophils; and prognosis of patients with SCN4 have not been fully elucidated. Methods: Two Chinese pediatric patients with G6PC3 mutations were enrolled in this study. Clinical data, genetic and immunologic characteristics, and neutrophil function were evaluated in patients and controls before and after granulocyte colony-stimulating factor (G-CSF) treatment. Results: Both patients had histories of pneumonia, inguinal hernia, cryptorchidism, and recurrent oral ulcers. Patient 1 also had asthma and otitis media, and patient 2 presented with prominent ectatic superficial veins and inflammatory bowel disease. DNA sequencing demonstrated that both patients harbored heterozygous G6PC3 gene mutations. Spontaneous and FAS-induced neutrophil apoptosis were significantly increased in patients, and improved only slightly after G-CSF treatment, while neutrophil respiratory burst and neutrophil extracellular traps production remained impaired in patients after G-CSF treatment. Conclusion: G-CSF treatment is insufficient for patients with SCN4 patients, who remain at risk of infection. Where possible, regular G-CSF treatment, long-term prevention of infection, are the optimal methods for cure of SCN4 patients. Closely monitor the possibility of leukemia in SCN4 patients is necessary. Once leukemia occurs in SCN4 patients, hematopoietic stem cell transplantation is the most important choice of treatment.